2011
DOI: 10.1007/s12011-011-9216-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Zinc, Manganese, Copper, and Selenium Chelates on Colostrum Production and Reproductive and Lameness Indices in Adequately Supplemented Holstein Cows

Abstract: The current study aimed to investigate if different sources of supplemental zinc (Zn), manganese (Mn), copper (Cu), and selenium (Se) fed to dry and lactating dairy cows affect reproductive performance, lameness status, and colostrum production. The experiment was carried out on 60 multiparous non-lactating Holstein cows in a commercial dairy herd. The cows received randomly mineral mixtures in three treatment groups containing inorganic, 25% organic-75% inorganic, or 50% organic-50% inorganic forms of Zn, Mn,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
1
7
1
1
Order By: Relevance
“…In the present trial, the colostrum quality (IgG concentration) was not affected by the form of minerals, for this same reason. This observation was in accordance with previous findings on Holstein cows (Karkoodi et al, 2012). Awadeh et al (1998) have demonstrated that Se supplementation of deficient beef cows may improve the IgG concentration in the colostrum.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present trial, the colostrum quality (IgG concentration) was not affected by the form of minerals, for this same reason. This observation was in accordance with previous findings on Holstein cows (Karkoodi et al, 2012). Awadeh et al (1998) have demonstrated that Se supplementation of deficient beef cows may improve the IgG concentration in the colostrum.…”
Section: Discussionsupporting
confidence: 94%
“…The effects of the form of Zn and Cu supplementation are the subject of several studies, which have conflicting results. Some authors have reported no effect of the source of Zn or Cu on their blood status, immune response, reproductive performance, lameness score or colostrum/milk production (Karkoodi et al, 2012;Wang et al, 2013), whereas other authors observed an enhanced immune response of early lactation dairy cows fed chelated sources of Zn and Cu compared to cows supplemented with the same amount of inorganic sources (Nemec et al, 2012). In the present study, no significant difference between treatment groups could be demonstrated.…”
Section: Discussioncontrasting
confidence: 77%
“…Because lameness is a process that can develop at different rates depending on the underlying pathology, the absence of differences in locomotion score might not necessarily indicate that AAC and INO cows had a similar supply of trace minerals. Karkoodi et al (2012) did not detect differences in locomotion score in peripartal cows fed diets supplemented with inorganic trace minerals (control), 25% organic:75% inorganic, and 50% organic:50% inorganic forms of Zn, Mn, Cu, and Se from −21 to 90 DIM. This indicates that, if nutritionally driven, lameness is the ultimate consequence of a long-term condition (e.g., limited supply of trace minerals or rumen acidosis), and locomotion score might not be suitable for determining short-term trace mineral imbalance.…”
Section: Locomotion Scorementioning
confidence: 76%
“…Deficiencies of Cu have been associated with retained placenta, embryonic death and decreased conception rates and anoestrus (8). Copper deficiency is also associated with depressed oestrus, silent heats and reduced conception rate (21).…”
Section: Effect Of Mineralsmentioning
confidence: 99%